2021
DOI: 10.1038/s41598-021-03172-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ocular findings regardless of visual acuity status in older adults from the Brazilian Amazon Region

Abstract: Recently, it has been recommended that population-based studies report not only frequencies of vision impairment and blindness but also any ocular abnormalities that might lead an individual to seek for eyecare services. The current study aimed to determine prevalence of ocular findings regardless of visual acuity (VA) status in older adults from the Brazilian Amazon Region. Disturbances were grouped into: Eyelids; Anterior Segment; Posterior Segment; Increased intraocular pressure; and Overall Globe. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
6
0
5
Order By: Relevance
“…2 Several population-based studies in humans have reported increased risk of cataracts ranging from 6% to 24% for each increasing year in age, similar to our finding of 20%. 2,36,38,39 Similarly, a higher frequency of retinal drusen is expected in older individuals. 40,41 Our findings indicate a frequency of retinal drusen of 15% in the population and its significant association with age, with the odds of having drusen increasing by 9% for each year of age.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2 Several population-based studies in humans have reported increased risk of cataracts ranging from 6% to 24% for each increasing year in age, similar to our finding of 20%. 2,36,38,39 Similarly, a higher frequency of retinal drusen is expected in older individuals. 40,41 Our findings indicate a frequency of retinal drusen of 15% in the population and its significant association with age, with the odds of having drusen increasing by 9% for each year of age.…”
Section: Discussionmentioning
confidence: 97%
“…that age was not a significant predictor of IOP. 31 Results from human studies are also variable, with some reports indicating higher IOP, 32 lowerIOP, 33,34 or no IOP association 35,36 in older individuals relative to younger individuals. Finally, we found a positive association between IOP and weight, which is in agreement with expectations and previous research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decade later, the same methodology was applied in Northern Brazil (Amazon region), and a lower importance of glaucoma was found (7.5% of all cases of blindness, only behind cataract) 64 . In this Brazilian population, glaucoma cupping was found in 8.8% of the subjects (adults with 45 years and older; all visual acuity groups included) 65 …”
Section: Comprehensive Studies On Blindness and Visual Impairmentmentioning
confidence: 91%
“…64 In this Brazilian population, glaucoma cupping was found in 8.8% of the subjects (adults with 45 years and older; all visual acuity groups included). 65 The Barbados eye study, a population-based survey in the Caribbean, reported that open angle glaucoma and cataract were the main causes of blindness. Each one represented 28.0% of all blindness, with 4.0% of cases having both diagnosis.…”
Section: Comprehensive Studies On Blindness and Visual Impairmentmentioning
confidence: 99%